Surface Dangling Bond Effect on Magnetic Property of Mn-doped ZnO Nanowires - N, Tsogbadrakh; Choi, Eun-Ae; Lee, Woo-Jin; K. J, Chang (Scientific transaction of the National University of Mongolia. Physics, 2022)
We investigate the magnetic properties of Mn-doped ZnO nanowires (NWs) using the local spin density approximation (LSDA) and the LSDA+U approach, where U represents the on-site Coulomb interaction. In carrier-free (Zn,Mn)O NWs, the majority Mn ta states are fully occupied, leading to an antiferromagnetic ground state. We examine the effect of additional p-type doping on the ferromagnetism by considering surface O dangling bonds. Localized hole carriers are generated in the majority ta states and promote a ferromagnetic ordering via double exchange interactions, similar to the trend of bulk (Zn,Mn)O. The ferromagnetic coupling tends to increase with increasing of the hole carrier density.